THE DIFFERENCE IN COLOR CHANGE OF PREHEATED AND NON-PREHEATED NANOFILLER COMPOSITE RESIN AFTER IMMERSION IN NON-INSTANT AND INSTANT COFFEE - Sri Ainur Astutik; Benni Benyamin; Rosa Pratiwi (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: One of the aesthetic issues in using composite resin is the color change. This study aimed to compare the color changes of preheated and non-preheated nanofiller composite resin soaked in non-instant coffee and instant coffee.Method: This study involved 24 round composite resins with a diameter of 12 mm and a thickness of 2 mm. The samples were divided into two groups (n=12); group I was prepared at 68°C and group II was prepared at room temperature. After curing, the samples were immersed in distilled water at 37°C for 24 hours before being measured with a UV-vis spectrophotometer. Each group was divided into two sub-groups (n=6), one soaked in non-instant coffee and the other in instant coffee for three days, and the final color was measured. The data was analyzed using two independent t-tests with a significance level of α =0.05.Result: Two independent t-tests revealed a significant difference between preheated and non-preheated nanofiller composite resins soaked in non-instant coffee (p<0.05), as well as a significant difference between preheated and non-preheated nanofiller composite resins soaked in instant coffee (p<0.05).Conclusion: The preheating was effective to improve the color stability of composite resin after immersion in non-instant coffee and instant coffee.